سيمياء السرد في رواية عازفة البيكادللي - الألمعي, فاطمة (University of Eloued جامعة الوادي, 2024)
سيمياء السرد في رواية عازفة البيكادللي يحاول هذا البحث الكشف عن علامات النص الروائي العربي عامة والجزائري خاصة؛ من خلال تتبع المسارات الصورية في رواية عازفة البيكاديللي للروائي الجزائري (واسيني الأعرج)؛ الذي جعل المكان شخصية أساس تدور حولها جميع الأحداث، فكان موضوعًا فاعلًا داخل النص الروائي؛ إذ كان مسرح قصر البيكادللي وجريمة حرقه العامل الذي أسس الصراع بين الذوات داخل المتن الحكائي، الأمر الذي فرض وجود مساعدين ومعارضين لهذا الحدث. انطلاقا من هذا الطرح سنقارب الرواية مقاربة سيميائية، مرتكزين في ذلك على سيمياء السرد لغريماس؛ باعتبارها المنهج الأنسب في معرفة الذوات المتصارعة، وكيفية انتقال ملفوظات الحالة إلى ملفوظات التحول وغيرها. فالدراسة تشمل مستويين: مستوى سطحي؛ يركز على شكل الشكل، ومستوى عميق؛ يركز على شكل المضمون، الذي سندرك من خلاله الثنائيات الضدية، ونصل إلى مستويات التأويل، والمربع السيميائي. Semitic-narrative in the novel of piccadilly pianist This study tries to uncover the novel textual signs in Arabic generally and Algerian specifically. This is achieved by tracing the visual paths in the novel 'The Piccadilly Pianist' by the Algerian novelist Waciny Laredj who made the place the main character where all events revolve around it. This has made it an effective element in the narrative text. The Piccadilly Palace stage and its arson crime was the factor behind the establishment of the struggle among the selves in the narrative structure which lead to the existence of supporters and opponents to this event. Based on this approach, we will approach the novel with a semiotic approach, relying on Grimas' semiotic of narrative considering it the most suitable method to understanding the conflicting selves and how the utterances of state were transformed to utterances of doing and more. The study contains two levels: a surface level that focuses on the shape of the figure and a deep level that focuses on the content that helps us understand opposite binaries, reach levels of interpretation and reach the semiotic square. Key words: semiotic, narrative, Piccadilly, semiotic square
مقال. مجلة علوم اللغة العربية وآدابها . مج16 . ع.02. جامعة الوادي
Keywords: السيمياء - السرد - البيكادللي - المربع السيميائي